Analyzing The Nexus Between Digital Financial Inclusion, Economic Growth, and Environmental Sustainability Impact in ASEAN Region - Taufik, Nukman; Danarsari, Dwi Nastiti (Universitas Islam Negeri Raden Mas Said Surakarta, 2025)
Purpose: This study aims to examine the impact of digital financial inclusion—proxied by debit card usage and ATM availability—on both economic growth and environmental sustainability across 11 ASEAN member countries during the period from 2010 to 2023. Method: Using panel data regression analysis, the study employs the Feasible Generalized Least Squares (FGLS) estimation method to analyze the relationship between financial inclusion, economic growth, and carbon emissions. Results: The analysis reveals a positive and significant relationship between debit card penetration and economic growth, suggesting that greater digital financial access contributes to economic performance. Conversely, the relationship between ATM availability and economic growth appears inconsistent. Implication: These findings underscore the need for policymakers, financial regulators, and development agencies to design financial systems that not only promote growth but also incorporate environmental safeguards. Originality: This research contributes to the literature by integrating digital financial inclusion metrics within an EKC framework to simultaneously evaluate economic and environmental outcomes in developing economies.